AGING AS AN INDICATOR OF CHANGES IN VOICE AND SPEECH QUALITY - Ilić Savić, Ivana; Petrović-Lazić, Mirjana (HEALTH CARE, 2025)
During the aging process, certain changes occur in the voice and speech. A person's voice changes during aging, becoming more unstable, less flexible, and hoarseness occurs. This study aims to analyze the effects of aging on voice frequency, voice intensity, and the rhythm and tempo of speech. The literature was studied using electronic databases, in particular Google Scholar Advanced Search and the Serbian Library Consortium for Coordinated Acquisition - KoBSON. The results show that there is a deterioration in the acoustic parameters of the voice (voice frequency and intensity) with age. It has also been observed that the aging process in the voice is more pronounced in women than in men. This can be explained by hormonal changes that are especially pronounced in women during menopause. After the age of sixty, the intensity of the voice becomes lower regardless of the person's gender. Depending on the person's age, the rhythm and tempo of speech also change. It was found that older subjects take longer to pronounce certain sounds, which is associated with a delay in the onset of phonation when pronouncing alveolar and bilabial sounds, which is most often attributed to jaw degradation. Studies show that voice and speech aging occurs gradually and as expected, with clearly expressed consequences for everyday life, which should be taken into account in clinical practice in order to improve the quality of life of older people.
Keywords: aging, voice frequency, voice intensity, rhythm and pace of speech